The turf-forming alga Gelidium crinale (Florideophyceae, Rhodophyta) on Atlantic Patagonian coasts - Croce, Maria Emilia (2013)
We describe for the first time the morphology of Gelidium crinale from its natural habitat in Atlantic Patagonia with special consideration of diagnostic characters. Observations and morphometric measurements were done on fresh specimens using scanning electron and inverted light microscopy. This report is a new record for Atlantic Patagonian coasts. The thalli comprise prostrate and erect axes; they are subterete at the base and compressed to flattened at the apices. The basal parts are scarcely and irregularly branched, while the apical parts are highly ramified and subdichotomously branched. The lengths of thalli and the ramification patterns differ from previous descriptions, and were variable between seasons and life history phases. ´Brush-like´ haptera confirmed the identity of the algae as members of the Gelidiaceae. Internal rhizoidal filaments are abundant and distributed in groups throughout the medulla. The life history was of the ´Polysiphonia -type´ ; occurrences of carposporophytes and tetrasporophytes were variable.